Contemporary Pedagogical Practices of Translation Skills in ESL Classrooms - Malik, Amir Hafeez; Seemab, Syed Waseem Azhar; Khudai, Unaiza; Rashid, Abdul (Pakistan Journal of Humanities and Social Sciences, 2023)
The present study explores the contemporary pedagogical practices of translation skills in undergraduate classrooms in Pakistan. Translation skills are essential components of the prescribed syllabuses and examinations. Classroom observations reveal that the students face problems in translation skills. Consequently, teaching and learning of translation skills need redesigning. The study aims to enhance awareness among students about the real implication of translation skills and suggest changes. The paradigm selected is the pragmatic analysis of contemporary unsuccessful pedagogical practices of translation skills. The data was collected from 321 undergraduate students of public and private institutions through a questionnaire. The data was analyzed descriptively. The findings reveal that the contemporary pedagogical practices of translation skills are less effective in enhancing translation skills as current translation practices focus on cramming translation rules and passages instead of developing students' autonomy. The research contributes to teaching and learning translation skills, especially for ESL teachers and learners. The outcomes of this research will lead future researchers to suggest further improvements in pedagogical practices of translation skills.